Surgical productivity recovery after the COVID-19 pandemic in Japan - Nakata, Yoshinori; Watanabe, Yuichi; Ozaki, Akihiko (Frontiers in Public Health, 2024)
Introduction Previous studies demonstrated that the surgical productivity regressed in 2020. This study therefore explored whether the COVID-19 pandemic had any significant lasting effect of reducing the surgical productivity in Japan. This is a retrospective observational study which is an extension of the previous ones. Methods The authors analyzed 18,805 surgical procedures performed during the study period from April 1 through September 30 in 2016–22. A non-radial and non-oriented Malmquist model under the variable returns-to-scale assumptions was employed. The decision-making unit (DMU) was defined as a surgical specialty department. Inputs were defined as (1) the number of assistants, and (2) the surgical duration. The output was defined as the surgical fee. The study period was divided into 42 one-month periods. The authors added all the inputs and outputs for each DMU during these study periods, and computed its Malmquist index, efficiency change and technical change. The outcome measures were its annual productivity, efficiency, and technical changes between the same months in each year. Results There was no statistically significant difference in annual productivity, efficiency, and technical changes between pre-pandemic and post-pandemic periods. Discussion No evidence was found to suggest that the COVID-19 pandemic has any significant lasting effect of reducing the surgical productivity.